2016
DOI: 10.1177/0885066616684122
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Lactic Acid and Base Deficit Values Obtained From Arterial and Peripheral Venous Samples in a Pediatric Population During Intraoperative Care

Abstract: Lactic acid and base deficit (BD) values are frequently monitored in the intensive care unit and operating room setting to evaluate oxygenation, ventilation, cardiac output, and peripheral perfusion. Although generally obtained from an arterial cannula, such access may not always be available. The current study prospectively investigates the correlation of arterial and peripheral venous values of BD and lactic acid. The study cohort included 48 patients. Arterial BD values ranged from -8 to 4 mEq/L and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The arterial lactate in many studies was demonstrated to be a biomarker for mortality in critically ill trauma patients [1]. Elevated arterial and venous lactate levels are associated with increased mortality; additionally, some studies have shown strong correlation between these two types of lactate values [27, 28]. Arterial or venous serum lactate level in trauma patients should be measured, because it is an easily obtainable biomarker of physiologic derangements in these patients that might also be used to notify the clinician of a potential increased risk of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial lactate in many studies was demonstrated to be a biomarker for mortality in critically ill trauma patients [1]. Elevated arterial and venous lactate levels are associated with increased mortality; additionally, some studies have shown strong correlation between these two types of lactate values [27, 28]. Arterial or venous serum lactate level in trauma patients should be measured, because it is an easily obtainable biomarker of physiologic derangements in these patients that might also be used to notify the clinician of a potential increased risk of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…The lactate level is more sensitive and easier to detect to act as an indicator to predict the prognosis of critically ill patients [3]. The imbalance between oxygen delivery and consumption will cause the accumulation of lactate, and lactate levels will rise sharply [4,5]. In addition, hypoperfusion can also result in an increased lactate level.…”
Section: Introductionmentioning
confidence: 99%
“…When combining max lactate at T24 with APACHE III, the lactate level is more sensitive and easier to detect and acts as an indicator to predict the prognosis of critically ill patients [3]. The imbalance between oxygen delivery and consumption will cause the accumulation of lactate, and lactate levels will rise sharply [4,5]. In addition, hypoperfusion can also result in an increased lactate level.…”
Section: Introductionmentioning
confidence: 99%